USE OF VIDEO MATERIALS IN TEACHING ENGLISH FOR SPECIFIC PURPOSES - V. V. Chmel (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The content of the paper was determined by the problem of multimedia application in teaching English for Specific Purposes. It also deals with the improvement of students' language skills as well as the development of socio-cultural and communicative competences in engineering students in the course of teaching English for Specific Purposes. The main principles of socio-cultural approach are distinguished. The most efficient multimedia aids are mentioned. The influence of multimedia aids at the English lessons on professional communicative skills of engineering students is analyzed. The teacher's role in teaching English for Specific Purposes is determined. Preparatory work for demonstrating video films is observed. The paper outlines the classroom activities and evaluates the usefulness of multimedia tools in teaching English for Specific Purposes. The author describes the stages and ways of work with video materials and gives recommendations how to use them in the ESP classroom. It is considered that active implementation of modern technologies has great influence on the teaching and learning process.